Fractional Integral Inequalities via Hadamard’s Fractional Integral - Weerawat Sudsutad; Sotiris K. Ntouyas; Jessada Tariboon (Abstract and Applied Analysis)
We establish new fractional integral inequalities, via Hadamard’s fractional integral. Several new integral inequalities are obtained, including a Grüss type Hadamard fractional integral inequality, by using Young and weighted AM-GM inequalities. Many special cases are also discussed.